1999
DOI: 10.1001/archinte.159.10.1082
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Pneumonia by Physical Examination

Abstract: The degree of interobserver agreement was highly variable for different physical examination findings. The most valuable examination maneuvers in detecting pneumonia were unilateral rales and rales in the lateral decubitus position. The traditional chest physical examination is not sufficiently accurate on its own to confirm or exclude the diagnosis of pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0
15

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(127 citation statements)
references
References 14 publications
2
110
0
15
Order By: Relevance
“…In humans, a French study performed in a hospital setting with better auscultation conditions than on a farm, the performance of thoracic auscultation was poor for detection of alveolar consolidation (sensitivity = 36%) 26. The available evidence concerning the use of lung sounds in a clinical setting is a recurrent debate in the human medical literature 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a French study performed in a hospital setting with better auscultation conditions than on a farm, the performance of thoracic auscultation was poor for detection of alveolar consolidation (sensitivity = 36%) 26. The available evidence concerning the use of lung sounds in a clinical setting is a recurrent debate in the human medical literature 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…9 Wipf et al searched the utility of physical chest findings and inter-rater reliability in patients suspected of having pneumonia, the sensitivity of physical examination to diagnose pneumonia was 47% to 69%, with a specificity of 58% to 75%. 16 They concluded that the most valuable signs in detecting pneumonia were unilateral rales and the traditional chest physical examination is not sufficiently accurate on its own to confirm or exclude the diagnosis of pneumonia. 16 A febrile transplant patient with signs and symptoms of pneumonia but a negative chest radiograph or a patient with a radiograph suggestive of a new mass lesion, CT scan of the thorax may be indicated in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…16 They concluded that the most valuable signs in detecting pneumonia were unilateral rales and the traditional chest physical examination is not sufficiently accurate on its own to confirm or exclude the diagnosis of pneumonia. 16 A febrile transplant patient with signs and symptoms of pneumonia but a negative chest radiograph or a patient with a radiograph suggestive of a new mass lesion, CT scan of the thorax may be indicated in the ED. In our study, patient X was a 35-year-old woman who presented to the ED with chest pain, cough and sputum.…”
Section: Discussionmentioning
confidence: 99%
“…La probabilidad de modificar el diagnóstico inicial de neumonía o la razón de verosimilitud (LR + ) del juicio clínico de los tres médicos de urgencia varió entre 1,5 y 4,8. Hallazgos similares fueron descritos por Wipf y cols, quienes evaluaron la precisión y variabilidad de los examinadores en la pesquisa de los signos clínicos específicos en pacientes con y sin diagnós-tico de neumonía 39 . Los autores concluyeron que los hallazgos semiológicos pesquisados en el examen de tórax no permiten confirmar ni excluir con seguridad el diagnóstico de neumonía, existiendo gran variabilidad interobservador en la pesquisa de hallazgos semiológicos específicos (Tabla 7).…”
Section: A R T í C U L O D E R E V I S I ó Nunclassified
“…consultan por fiebre o síntomas respiratorios agudos [27][28][29][30][31][37][38][39][40][41] . Ninguna de las reglas de decisión descritas en la literatura han sido superiores al juicio clínico en el diagnóstico de neumonía, y aún no existen estudios que hayan examinado su real aporte en la evaluación y manejo de los pacientes que consultan por síntomas respiratorios o fiebre en los servicios de asistencia ambulatoria.…”
Section: Juicio Clínicounclassified